2015
DOI: 10.3892/mmr.2015.3924
|View full text |Cite
|
Sign up to set email alerts
|

CD14 knockdown reduces lipopolysaccharide-induced cell viability and expression of inflammation-associated genes in gastric cancer cells in vitro and in nude mouse xenografts

Abstract: Abstract. The present study examined the role of CD14 in the regulation of lipopolysaccharide (LPS)-induced effects on gastric cancer cells. MGC-803 cells were stably transfected with CD14 short hairpin (sh)RNA and treated with LPS, followed by assessment of cell proliferation, apoptosis and gene expression using a cell counting kit-8 assay, flow cytometry, reverse transcription-polymerase chain reaction and western blot analysis, respectively. The cells subjected to CD14 knockdown were treated with 10 g/ml LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Moreover, LPS acts as endotoxin involving in induction of strong inflammatory responses [18, 19]. As Li et al [20] reported that LPS induced gastric cancer cell proliferation, inhibited apoptosis and increased the secretion of IL-1β, IL-6, IL-12 and TNF-α. Furthermore, Wang et al [21] confirmed that LPS could induce pro-inflammatory cytokines of IL-1β, IL-6, IL-8 and TNF-α productions in macrophage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LPS acts as endotoxin involving in induction of strong inflammatory responses [18, 19]. As Li et al [20] reported that LPS induced gastric cancer cell proliferation, inhibited apoptosis and increased the secretion of IL-1β, IL-6, IL-12 and TNF-α. Furthermore, Wang et al [21] confirmed that LPS could induce pro-inflammatory cytokines of IL-1β, IL-6, IL-8 and TNF-α productions in macrophage.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that FCER1G participates in a variety of immune functions and can be used as a prognostic marker for a variety of cancers (44)(45)(46). As a key component of the Toll-like receptor (TLR) signaling pathway, CD14 can promote tumor occurrence and development by regulating the activation of different signaling pathways in tumor cells or tumor infiltrating immune cells (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that FCER1G participates in a variety of immune functions and can be used as a prognostic marker for a variety of cancers ( 44 46 ). As a key component of the Toll-like receptor (TLR) signaling pathway, CD14 can promote tumor occurrence and development by regulating the activation of different signaling pathways in tumor cells or tumor infiltrating immune cells ( 47 50 ). Research on MS4A6A is mainly focused on Alzheimer’s disease, and there are also current studies showing that it can be used as a prognostic marker for tumors ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…As stated by Lee, et al,20 LPS contributes to the production of cell adhesion molecules, TNF-α, and activated NF-κB, and induces the adhesion/migration of monocytes to human umbilical vein endothelial cell. Li, et al21 reported that LPS triggers cell proliferation, suppresses apoptosis, and enhances the release of IL-1β, IL-6, IL-12, and TNF-α in gastric cancer. Our study showed that LPS significantly induces chondrocyte injury, reflected by decreased cell viability, increased apoptosis, and stimulation of IL-1β, IL-6, and TNF-α secretion in C28/I2 cells, which was similar with previous research reported by Sun, et al22…”
Section: Discussionmentioning
confidence: 99%